El ejercicio de las competencias reglamentarias por parte de Corte Constitucional y la Seguridad Jurídica. - Cajas Moncayo, Shanon Mishell (2023)
The present investigation is entitled "The exercise of regulatory powers by the Constitutional Court and legal certainty", which originates from the issuance of Resolution No. 012-CCE-PLE-2020 with which the application of the fraud, manifest negligence and inexcusable error, exercising a regulatory competence that is not provided for in Article 436 of the Constitution of the Republic of Ecuador. In this virtue, the purpose of this investigation, describe the powers of the Constitutional Court have been exercised properly and in accordance with the limits imposed by the legal system itself. For the fulfillment of this investigation, it will be developed in three parts: first through the treatment of the constant theoretical framework in 3 units called: the first, the Constitutional Court; the second, legal certainty; and, the third, the violation of the right to legal certainty with the exercise of regulatory powers of the Constitutional Court. The appropriate methodological design for a social legal investigation, through the legal-doctrinal, legal-analytical and descriptive method; mixed research approach; types of documentary, descriptive and field research; non-experimental research design. Additionally, information has been collected thanks to the research instruments, with which it has been possible to draw conclusions and recommendations according to the problem investigated.